2011
DOI: 10.3851/imp1820
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of Toll-Like Receptors and Their Pathways in Viral Hepatitis

Abstract: Toll-like receptors (TLRs) are an important part of the innate immune response to a variety of pathogens including hepatic viral infections. Activation of TLRs stimulates a complex intracellular signalling cascade that results in production of proinflammatory cytokines and interferons important for antiviral responses as well as induction of the adaptive arm of the immune system. There is substantial evidence for an important role for TLRs and TLR-mediated signalling in the pathogenesis and outcomes of hepatit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 165 publications
(226 reference statements)
0
11
0
1
Order By: Relevance
“…These are located in the fourth exon and affect the extracellular domain of the molecule, which is associated with receptor hyporesponsiveness but not receptor expression. [15][16][17][18] TLR4 is involved in the pathogenesis of various viral infections [19][20][21][22][23][24] including hepatitis B (HBV) and hepatitis C (HCV) viruses.…”
Section: Introductionmentioning
confidence: 99%
“…These are located in the fourth exon and affect the extracellular domain of the molecule, which is associated with receptor hyporesponsiveness but not receptor expression. [15][16][17][18] TLR4 is involved in the pathogenesis of various viral infections [19][20][21][22][23][24] including hepatitis B (HBV) and hepatitis C (HCV) viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis C virus (HCV), a single‐stranded (ss) RNA virus, infects more than 170 million people worldwide . The clinical outcome of HCV infection is highly variable, and genetic factors involving innate immunity are likely to affect disease susceptibility and progression after infection . The role of Toll‐like receptor 8 (TLR8) in host defence against viruses suggests that TLR8 is a suitable marker for exploring the linkage between variants in innate‐immune genes and susceptibility to viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated an association between TLR7 gene polymorphisms and infection diseases in different populations; however, only one study showed that the TLR7 SNP rs179009 is related to susceptibility to HCV infection in Taiwanese patients in China 17. Most TLR SNPs, except TLR9 SNPs, have been investigated in terms of their relationship with chronic HCV 18. In the present study, we assessed the frequencies of TLR7 (rs179009) and TLR9 (rs187084) SNPs, in order to clarify the role of TLR7, TLR9 polymorphism in HCV infection.…”
Section: Introductionmentioning
confidence: 99%